A twin study of mitochondrial DNA polymorphisms shows that heteroplasmy at multiple sites is associated with mtDNA variant 16093 but not with zygosity. - Toby Andrew; Cassandra D Calloway; Sarah Stuart; Sang Hoon Lee; Raj Gill; Gail Clement; Philip Chowienczyk; Tim D Spector; Ana M Valdes (PLoS ONE, 2011)
The mitochondrial theory of ageing proposes that damage to mitochondria and diminished mitochondrial DNA (mtDNA) repair are major contributors to cellular dysfunction and age-related diseases. We investigate the prevalence of heteroplasmy in the mtDNA control region in buccal swab and blood derived samples for 178 women from the TwinsUK cohort (41 DZ pair 39 MZ pairs, 18 singletons, mean age 57.5 range 28-82) and its relationship to age, BMI and fasting insulin and glucose serum levels. The overall estimated prevalence of heteroplasmy for both tissues in the control region measured for 37 sites was 17%. The prevalence of heteroplasmy was higher among the older half of the study subjects than in the younger half (23% vs 10% p<0.03), primarily reflecting the increase in the prevalence of a heteroplasmic dinucleotide CA repeat in variable region II (VRII) with age. The VRII 523-524 heteroplasmic site (heteroplasmic in 25 subjects) was also associated with a decrease in BMI. In addition, concordance rates for common heteroplasmy were observed to be near complete for both dizygotic (DZ = 94%) and monozygotic twin pairs (MZ = 100%), consistent with previous reports that suggest variation in heteroplasmy rates between generations are determined by bottlenecks in maternal transmission of mitochondria. Differences in the prevalence of heteroplasmy were observed overall between samples derived from buccal swabs (19%) and blood (15%, p<0.04). These were particularly marked at position 16093 of hypervariable region I (HVI, 7% vs 0%, respectively, p<4×10(-11)). The presence of the C allele at position 16093 in blood was associated with the presence of heteroplasmy in buccal swabs at this position (p = 3.5×10(-14)) and also at VRII (p = 2×10(-4)) suggesting a possible predisposing role for this site in the accumulation of heteroplasmy. Our data indicate that BMI is potentially associated with control region heteroplasmy.